2018
DOI: 10.1002/jcla.22663
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic trisomy 22 in a 4‐year‐old boy with congenital heart disease and general hypotrophy: A case report

Abstract: Background Trisomy 22 mosaicism is a rare autosomal anomaly with survival compatibility. Recognition of the complete trisomy 22 which is incompatible with life from the mosaic form is critical for genetic counseling. Affected mosaic cases have prevalent clinical presentations such as webbed neck, developmental delay, abnormal ears, cardiac disorders, and microcephaly. Phenotype of these patients is milder than full chromosomal aneuploidy, and the severity of the phenotype depends on the count of trisomic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Mosaic trisomy 22 is rare, with at least 22 cases reported. Various types of CHDs were noted in 76% of a series of 21 patients (Abdelgadir et al, ; Kalyina et al, ). It is difficult to discern the cause of early mortality in patients with complete or mosaic trisomy 22, whether it is cardiac in nature, or some other etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaic trisomy 22 is rare, with at least 22 cases reported. Various types of CHDs were noted in 76% of a series of 21 patients (Abdelgadir et al, ; Kalyina et al, ). It is difficult to discern the cause of early mortality in patients with complete or mosaic trisomy 22, whether it is cardiac in nature, or some other etiology.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, karyotype analysis, whole‐exome sequencing (WES) in the case (CHD‐7) that we found structural changes in his chromosomes, and GATA4 variant were checked; briefly, peripheral blood from all the patients was collected in heparin and EDTA tubes, both. Heparinized blood was used for karyotyping, based on the standard protocols as described previously, and EDTA‐treated samples for DNA extraction. The study is performed in accordance with the Helsinki Declaration and has been approved by the Rajaei Cardiovascular, Medical, and Research Center (RHC.AC.IRREC.1395.46; December 24, 2016) and Zanjan University of Medical Sciences (ZUMS.REC.1396.145; June 21, 2017) Ethics Committees.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, karyotype analysis, whole-exome sequencing (WES) in the case (CHD-7) that we found structural changes in his chromosomes, and GATA4 variant were checked; briefly, peripheral blood from all the patients was collected in heparin and EDTA tubes, both. Heparinized blood was used for karyotyping, based on the standard protocols as described previously 18…”
Section: Study Subjects and Samplesmentioning
confidence: 99%
“…Histological abnormalities included enlarged myocyte nuclei with expanded cytoplasm. This condition has been reported to have phenotypic associations with mosaic trisomy 22 [ 10 ]. A 19-month male infant born to consanguineous parents with a history of intrauterine growth restriction and a sudden movement deterioration was admitted to the hospital with bradycardia.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Histological abnormalities included enlarged myocyte nuclei with expanded cytoplasm. This condition has been reported to have phenotypic associations with mosaic trisomy 22 [ 10 ].…”
Section: Case Descriptionmentioning
confidence: 99%